Evaluation Of The Flow Discharge Of The Quillcay River Sub-Basin – Peru In The Face Of Climate Change - Jara, Flor; Santiago, Alexzander; Mejía, Abel; Colonia, Pedro; Mejía, Teófanes; Revelo, Gerardo (Migration Letters, 2024)
In recent decades, climate change has had an impact on meteorological alterations, so in many places they are leading to the high rainfall and droughts manifested by ENSO (El Niño Southern Oscillation). Geospatial technologies, together with hydrometeorological information, have made it possible to make hydrological studies more accurate and detailed. In this research, a methodology for flow discharge is proposed using HEC-RAS (Hydrological Engineering Center – River Analysis System) and flow data modeled by SWAT (Solid and Water Assessment Tool) and HEC-HMS (Hydrologic Engineering Center’s Hydrologic Modeling System). 4 evaluation periods were determined during 1986 to 2016; In addition, 2 February dates of high occurrence of ENSO were determined, 1998 and 2016. The average results obtained for the depth time series are a mean of 3.75 m and a standard deviation of 3.19, minimum of 0 and maximum of 26.24m. The results in ENSO were depth ranging from 0 to 15 m, velocity from 0 to 2 m/s and WSE is from 837 to 902 m.